The relation between equity incentives and misreporting: The role of risk-taking incentives - Armstrong, Christopher S.; Larcker, David F.; Ormazabal, Gaizka; Taylor, Daniel J. (Journal of Financial Economics, 2013)
Prior research argues that a manager whose wealth is more sensitive to changes in the firm׳s stock price has a greater incentive to misreport. However, if the manager is risk-averse and misreporting increases both equity values and equity risk, the sensitivity of the manager׳s wealth to changes in stock price (portfolio delta) will have two countervailing incentive effects: a positive “reward effect” and a negative “risk effect.” In contrast, the sensitivity of the manager׳s wealth to changes in risk (portfolio vega) will have an unambiguously positive incentive effect. We show that jointly considering the incentive effects of both portfolio delta and portfolio vega substantially alters inferences reported in prior literature. Using both regression and matching designs, and measuring misreporting using discretionary accruals, restatements, and enforcement actions, we find strong evidence of a positive relation between vega and misreporting and that the incentives provided by vega subsume those of delta. Collectively, our results suggest that equity portfolios provide managers with incentives to misreport when they make managers less averse to equity risk.